Pengaruh Tenaga Kerja, Tingkat Pendidikan, Produk Domestik Regional Bruto (PDRB), Konsumsi, dan Investasi Terhadap Kemiskinan di Sumatera Utara - Matthew Nico Vendison; Rebecca Octavia Pangalerang; Fenny Fenny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
North Sumatra is facing the problem of high poverty rate. The issue of poverty increases every year. This research is aimed to examine the effect of labor, education level, Gross Regional Domestic Product (GRDP), consumption and investment on poverty in North Sumatra. The approach is quantitative and the data is processed. The research is quantitative and causal. The population in the research is the GRDP of North Sumatra for the 2017-2019 period as many as 29 districts/cities. The sample is 29 districts/cities within 3 years concluded with 87 sample data. The method of data analysis is multiple linear regression test. The result of the research is labour and GRDP has an effect on poverty in North Sumatra. Level of education, consumption and investment do not have an effect on poverty in North Sumatra. Education level, GDRP, consumption and investment have an influence on poverty in North Sumatra. Keywords : Labor, Level of Education, Gross Regional Domestic Product (GRDP), Consumption, Investment and Poverty.